An analysis of digital environment structuring and its impact on engagement: a case study of the Bandung City government’s social media accounts, Indonesia - Atnan, Nur; Sembada, Windhiadi Yoga (Frontiers in Communication, 2025)
In the era of digital transformation, social media has become a primary communication channel for local governments in fostering public engagement. This study analyzes how the structuring of the digital environment influences public engagement on the Instagram and Twitter (X) accounts of the Bandung City Government in 2022. Employing a qualitative case study approach, data were collected through in-depth interviews with social media administrators, active users, and practitioners. The findings reveal that account profiles (name and descriptions) and highlighted themes contribute to building identity and accessibility but do not significantly enhance engagement. In contrast, content design and feature optimization play a more substantial role in driving user interaction. Visually appealing content increases audience retention, while the use of interactive features strengthens two-way communication. This study contributes to digital engagement theory by underscoring the impact of digital environment structuring on public interaction. Practically, it offers insights for government social media administrators in designing more effective engagement strategies. This includes actionable recommendations for optimizing content formats, timing, and platform-specific features to improve citizen involvement.